Imine Resveratrol Analogues: Molecular Design, Nrf2 Activation and SAR Analysis - Li, Chang; Xu, Xiaofei; Wang, Xiu Jun; Pan, Yuanjiang (PLOS ONE, 2014)
Resveratrol is a natural phenol with protective effects against cancer and inflammation-related diseases. Its mechanism of action involves the activation of nuclear factor E2 p45-related factor 2 (Nrf2), which plays a key role in regulation of genes driven by antioxidant response element (ARE). Inspired by the effect of resveratrol, here we synthesized a series of imine resveratrol analogs (IRAs), evaluated their abilities to activate Nrf2 by using cell based ARE-reporter assay. After the first-round screening, preliminary and quantitative structure-activity relationship (SAR) was analyzed, and the structural features determining Nrf2 activation ability were proposed. Two novel IRAs were designed and subsequently synthesized, namely 2-methoxyl-3,6-dihydroxyl-IRA and 2,3,6-trihydroxyl-IRA. They were proved to be the most potent Nrf2 activators among the IRAs.